Ethnobotanical Study and Hedonic Evaluation with Cost Analysis of Banana (Musa paradisiaca L.) Stem Serum Preparation as an Anti-Aging Solution - Megawati, Fitria; Dewi, Ni Luh Kade Arman Anita; Agustini, Ni Putu Dewi; Antara, I Putu Satria; Ekayanti, Ni Luh Firda; Darmayanti, Ni Wayan (Borneo Journal of Pharmacy, 2024)
In skincare, particularly facial serums, the utilization of natural ingredients is crucial in addressing various skin issues, notably combating the effects of free radicals that contribute to wrinkles. This study explores the potential of banana (Musa paradisiaca L.) stem extract as an active ingredient in serum formulation due to its rich anthocyanin content known for antioxidant properties. Hedonic testing and cost analysis serve as initial steps in the marketing mix of a product. This research aims to assess the hedonic preferences of various M. paradisiaca stem serum formulations and analyze the production costs. A descriptive research method employing survey and observational techniques was utilized for data collection and descriptive analysis. Hedonic testing was conducted to gauge the personal preferences of panelists toward M. paradisiaca stem serum formulations. Three formulations (F1 with 4%, F2 with 8%, and F3 with 12% M. paradisiaca extract) were evaluated by 40 panelists. Cost analysis of serum production employed quantitative descriptive analysis, computing the cost per unit using a variable costing method. The hedonic evaluation results showed that F1 formulation was highly preferred (79.3%), followed by F2 (73.2%), and F3 (66.8%). Cost analysis using the variable costing method revealed a total production cost of IDR 614,000.00 for 10 packages of M. paradisiaca stem serum formulation, translating to an approximate unit price of IDR 61,400.00.